Efficacy and safety of different drugs in patients with HER2-positive gastric cancer: network meta-analysis - Jie Zhang; Chunluan Yuan; Xiao Ma (Systematic Reviews)
Abstract Background In the past decade, there has been a significant advancement in targeted therapy and immunotherapy, leading to the discovery of new drugs and changes in the treatment approach for patients with HER2-positive gastric cancer. Although several drugs are available for treating these patients, there is still no consensus on their selection, and there has been limited direct or indirect comparison among them. Objective To address this gap, a network meta-analysis was conducted to assess the efficacy and safety of different drugs used in the treatment of HER2-positive gastric cancer. Methods By searching through databases such as PubMed, Embase, Web of Science, and Cochrane Library, we identified 16 randomized controlled trials that involved a total of 4485 patients and utilized 9 different intervention measures. Results Based on the current evidence, compared with chemotherapy alone, the hazard ratio (HR) of overall survival (OS) and progression-free survival (PFS) in gastric cancer patients treated with nivolumab were [hazard ratio (HR): 2.61 95%confidence interval (CI) (1.51, 4.51)] and [hazard ratio (HR): 2.01 95% confidence interval (CI) (1.18, 3.42)], respectively. Compared with chemotherapy alone, the hazard ratio (HR) of overall survival (OS) and progression-free survival (PFS) in gastric cancer patients treated with trastuzumab deruxtecan were [hazard ratio (HR): 1.7 95% confidence interval (CI) (1.13, 2.56)] and [hazard ratio (HR): 2.13 95% confidence interval (CI) (1.42, 3.22)], respectively. It is suggested that nivolumab and trastuzumab deruxtecan can effectively prolong overall survival (OS) and progression-free survival(PFS) in patients with HER2-positive gastric cancer, while also reducing the risk of adverse events to some extent. Therefore, these two regimens, nivolumab and trastuzumab deruxtecan, are considered to be effective and safe options for the treatment of patients with HER2-positive gastric cancer. Conclusions In previous studies, trastuzumab-based chemotherapy has been a common treatment for HER2-positive gastric cancer. To a certain extent, our study provides a reliable direction for future treatment options for HER2-positive gastric cancer. Systematic review registration PROSPERO CRD42023420941